Education Of Family Medicinal Plants (TOGA) As Components Of Private Green Space Vegetation - Dienny Redha Rahmani (Comment: an International Journal of Community Development, 2021)
The true vegetation of the yard is not only filled with trees but also other vegetation strata such as shrubs. Generally, the plants planted are those that provide other benefits besides ecological functions. One of that function is as a herbal medicine. One of those functions is traditional herbal medicine. Traditional medicine has been empirically proven to use and can maintain body health from generation to generation. Indonesia Community plant this as family medicinal plant or known as TOGA. TOGA education is divided into two sessions, namely education on the types of toga that can be planted and education on processing TOGA into herbal medicine so that it can have health value. The benefits that can be obtained from this activity are that we can find out that in fact kitchen ingredients. Planting this type of plant has a positive impact on both humans and the environment as a constituent of private green spaces